2020
DOI: 10.3390/agronomy10111788
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Root Endophyte Pseudomonas brassicacearum CDVBN10 as Plant Growth Promoter for Brassica napus L. Crops

Abstract: Rapeseed (Brassica napus L.) is an important crop worldwide, due to its multiple uses, such as a human food, animal feed and a bioenergetic crop. Traditionally, its cultivation is based on the use of chemical fertilizers, known to lead to several negative effects on human health and the environment. Plant growth-promoting bacteria may be used to reduce the need for chemical fertilizers, but efficient bacteria in controlled conditions frequently fail when applied to the fields. Bacterial endophytes, protected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 107 publications
4
34
0
Order By: Relevance
“…These sequences do not allow a robust classification of the sequences at species level [ 67 ]. To obtain the most accurate identification at species level, there are nowadays massive parallel sequencing platforms with the potential to obtain nearly complete 16S rRNA gene sequences (~1500 bp), which allow a better identification of the microbiome at species level [ 35 , 37 , 68 ]. Moreover, amplicons of Pseudomonas housekeeping genes such as rpoB , rpoD , and gyrB [ 49 ] can be obtained for a more accurate identification at species level of those bacterial strains belonging to Pseudomonas .…”
Section: Pseudomonas Bacteria Are Broadly Assocmentioning
confidence: 99%
“…These sequences do not allow a robust classification of the sequences at species level [ 67 ]. To obtain the most accurate identification at species level, there are nowadays massive parallel sequencing platforms with the potential to obtain nearly complete 16S rRNA gene sequences (~1500 bp), which allow a better identification of the microbiome at species level [ 35 , 37 , 68 ]. Moreover, amplicons of Pseudomonas housekeeping genes such as rpoB , rpoD , and gyrB [ 49 ] can be obtained for a more accurate identification at species level of those bacterial strains belonging to Pseudomonas .…”
Section: Pseudomonas Bacteria Are Broadly Assocmentioning
confidence: 99%
“…These findings confirmed that in silico genome analyses are a good tool for detecting potential plant growth-promoting bacteria since the strains whose genome contains several genes involved in plant colonization and growth promotion mechanisms also display these mechanisms in vitro, and moreover, they showed good behavior in plant experiments carried out in microcosm conditions [26,32,33]. However, the incorporation of these strains in commercial inoculants requires conducting field experiments that have rarely been performed to date after the genome analysis of endophytic PGPB strains [27][28][29].…”
Section: Analysis Of Genes Involved In Plant Growth Promotionmentioning
confidence: 55%
“…However, the presence of these genes in the genome of a strain is not enough to ensure its effective performance on plants, and thus in silico genome mining should be accompanied by the analysis of plant effects, with field trials being the only way to verify the real potential of strains as crop biostimulants. Although this was the approach in some recent research on inoculating endophytic bacteria on non-legumes [27,28] and rhizobia on common bean [29], there are no studies relating in silico analysis and field performance for endophytic bacteria inhabiting legume nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Pseudomonas have been identified in human and animal related sources, plants, soil, water environments, psychrophilic environments, and other environmental niches and hosts [ 3 , 4 , 5 ]. Also, some species of this genus are known to play relevant roles in their hosts, such as P. aeruginosa , which causes human lung infections [ 6 ], species belonging to the P. fluorescens lineage, which are able to promote plants growth [ 7 , 8 ], or even some diverse species suggested to interfere with insects’ biology [ 9 , 10 ], amongst many other cases. The multiplicity of environments where Pseudomonas grow and diversify has led to the broad evolution of its members, making it one of the most diverse bacterial genera.…”
Section: Introductionmentioning
confidence: 99%